Helmholtz Equation Applied to the Vertical Fixed Cylinder in Wave Using Boundary Element Method - Ghassemi, Hassan; Gharechahi, Ataollah; Soleimani, Kaveh; Ketabdari, Mohammad Javad (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
Helmholtz equation is employed to the wide variety of engineering problems. This paper presents using Helmholtz equation to the vertical fixed cylinder against regular wave by the boundary element method (BEM). The results are included the pressure and forces on the cylinder. The present results are compared with available data, and show in good agreement. The results show that up to a certain dimensionless wave length, the wave force has a direct relation with the dimensionless wavelength, while after the force decreases with the increase of the dimensionless wave length.